2021
DOI: 10.3390/cells10051169
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormone Receptor Signaling in Bladder Cancer: A Potential Target for Enhancing the Efficacy of Conventional Non-Surgical Therapy

Abstract: There have been critical problems in the non-surgical treatment for bladder cancer, especially residence to intravesical pharmacotherapy, including BCG immunotherapy, cisplatin-based chemotherapy, and radiotherapy. Recent preclinical and clinical evidence has suggested a vital role of sex steroid hormone-mediated signaling in the progression of urothelial cancer. Moreover, activation of the androgen receptor and estrogen receptor pathways has been implicated in modulating sensitivity to conventional non-surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…Bladder cancer (BCa), predominantly urothelial carcinoma, is a common malignant genitourinary tumor (1,2). Men are 3 to 4 times more frequently diagnosed with bladder cancer than women; however, women tend to be diagnosed with more advanced disease at presentation and have less favorable outcomes after treatment (1,(3)(4)(5). Female patients with urothelial carcinoma of the bladder have been shown to have worse cancer specific survival, overall survival and recurrencefree survival (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer (BCa), predominantly urothelial carcinoma, is a common malignant genitourinary tumor (1,2). Men are 3 to 4 times more frequently diagnosed with bladder cancer than women; however, women tend to be diagnosed with more advanced disease at presentation and have less favorable outcomes after treatment (1,(3)(4)(5). Female patients with urothelial carcinoma of the bladder have been shown to have worse cancer specific survival, overall survival and recurrencefree survival (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Although resistance to CDDP-based chemotherapy is not uncommonly seen in patients with urothelial cancer, its underlying mechanisms are not fully understood. Meanwhile, AR activation in bladder cancer cells has been implicated to be associated with chemoresistance [ 12 , 13 , 14 , 15 , 21 , 22 , 23 , 24 ]. In the present study, we further investigated the role of GULP1, as a downstream target of AR, in CDDP resistance, using bladder cancer cell lines as well as surgical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of AR expression should therefore be elevated in high-grade/muscle-invasive bladder cancers compared with low-grade/non-muscle-invasive tumors. However, conflicting data exist regarding the expression of AR mRNA [ 19 , 37 ] and protein (as reviewed in [ 11 , 12 ]) in different grades/stages of bladder tumors. Specifically, in a meta-analysis of immunohistochemical studies, AR expression was shown to be rather significantly down-regulated in high-grade or muscle-invasive tumors [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 90% of bladder cancer is superficial growth, having the characteristics of polycentricity, easy recurrence, and metastasis and, unfortunately, the five-year survival rate of patients with stage IV bladder cancer is only 15% [3]. Presently, the clinical treatment of bladder cancer is mainly surgery, supplemented by radiotherapy and chemotherapy, but there is no ideal targeted therapy [4,5].…”
Section: Introductionmentioning
confidence: 99%